PERANAN H. HIMRON SAHEMAN DALA M MEMPERTAHANKAN KEMERDEKAAN DI RENGAT PADA TAHUN 1949 - Nurmi Suari; Bunari Bunari; Ridwan Melay (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: H. Himron Saheman is one of the fighters in maintaining independence in Rengat in particular and Riau Province generally. In addition H. Himron Saheman has many roles in maintaining independence in Riau Province. One of them in Rengat. At the time of the Dutch Military Aggression II occurred. H. Himron Saheman and other Soldiers tried to reclaim the town of Rengat that had been occupied by the Dutch by way of guerrilla attacks. In addition to his role in the field of Military he also has a role in terms of advancing the Riau region such as, as one of the founders of Building Juang 45 Riau Province, the originator for the construction of the Taman Makam Bahagia Kusuma Bhakti, Commander Kodim 0301, Becoming Bengkalis Regent, Chief Inspectorate Riau, Chairman of the Riau Regional House of Representatives, Member of the People's Consultative Assembly of the Republic of Riau, Chairman of PEPABRI Riau, chairman of DHD 45 Riau Province, and chairman of Legion Veteran of the Republic of Indonesia (LVRI) Riau Province. To know the role of H. Himro Saheman as a warrior character, the method used is qualitative which is a research method whose findings and sources are not obtained from statistical procedures or other calculations. This type of research is a field study to explore and examine data related to the title. The respondents from this research are H. Himron Saheman, outgoing party and relatives of H. Himron Saheman. Data collection techniques used were interviews, documentation and related books in the role of H. Himron Saheman in maintaining independence in Rengat and Riau Province.Keywords: H. Himron Saheman, Rengat, Indragiri Hulu, Dutch Military Aggression II, Event 5January 1949 in Rengat.